PENDAMPINGAN STRATEGI KUALITAS LAYANAN TAMBAHAN (AUGMENTED PRODUCT) PADA USAHA IILA SALON - Tri Palupi Robustin (STIE Mandala Jember, 2021)
The problem with this salon business is the lack of knowledge about optimal service strategies, especially to attract consumers to come back to the salon. Based on the background and problems, this community service activity aims to provide assistance to Iila Salon owners related to the quality of additional services (augmented products). Additional service quality strategy after sale in the form of giving away free hair cap (shampoo headgear) and providing free shampooing for customers who have come to the salon for treatments such as rebonding and smoothing. The strategy aims to make customers satisfied with the service and ultimately have an impact on loyalty. The results of the implementation of this community service activity are: (1) Survey of business locations so that information obtained Iila Salon place and approval of cooperation contracts with partners / owners of salons. (2) Interview with the owner of Iila Salon, information was obtained related to the history of the establishment of the business and the problems faced so that the community service team can provide solutions related to the problem. (3) Provide assistance in the form of rebonding drugs, hair stamps, shampoos and conditioners so that salon owners can later implement additional service quality strategies (augmented products) that have been taught by the community service team. Keywords : Iila Salon, Augmented Product, Service Quality